MULTIMODAL TEXTS IN PORTUGUESE LANGUAGE CLASSROOM - Weber, Marcia; Seganfredo Santos, Leandra Ines [UNESP] (Univ Estado Mato Grosso, 2016)
This paper aims to socialize practices of Portuguese Language teaching classroom with two classes of the 3rd phase of the 3rd cycle from a state school of Mato Grosso municipality. It is an interventional proposal with the use of the Didactic Sequence as a methodological procedure. It purposes to develop written procedures with students through the appropriation of digital technologies and multimodal texts production, culminating in the development of infographics. The results show that the students were able to relate verbal to the non-verbal information, building a text with coherence and cohesion, enabling easy understanding.
Keywords: Portuguese Language teaching; Didactic Sequence; infographics; authorship